Analysing factors influencing stated preference of the administrative and academic employees towards telecommuting in IIUM Campus, Gombak - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (2013)
Telecommuting is seen as a Transportation Demand Management (TDM) tool that can reduce congestion by eliminating a trip or shifting it out of the peak travel period by allowing employees to work from home. This paper constitutes an empirical study on factors influencing the choice of telecommuting adoption in the International Islamic University Malaysia (IIUM) among the administrative and academic employees. Methods of analysisconducted in this study are chi-square test and spearman’s correlation coefficient. The results showed that age, marital status, presence of children age 12 and less and frequency of face to face communication were significantly associated with the preference towards telecommuting. Furthermore, this research has tested the relationship between facilitators of telecommuting and willingness to telecommute as well as relationship between inhibitors of telecommuting and the willingness to perform telecommuting. Lastly, the study concludes with suggestions and recommendations to increase the penetration of telecommuting in IIUM.